Caffeine–N-phthaloyl-β-alanine (1/1) - Bhatti, Moazzam H. (International Union of Crystallography, 2012)
The title co-crystal [systematic name: 3-(1,3-dioxoisoindolin-2-yl)propanoic acid–1,3,7-trimethyl-1H-purine-2,6(3H,7H)-dione (1/1)], C(8)H(10)N(4)O(2)·C(11)H(9)NO(4), is the combination of 1:1 adduct of N-phthaloyl-β-alanine with caffeine. The phthalimide and purine rings in the N-phthaloyl-β-alanine and caffeine molecules are essentially planar, with r.m.s. deviations of the fitted atoms of 0.0078 and 0.0118 Å, respectively. In the crystal, the two molecules are linked via an O—H⋯N hydrogen bond involving the intact carboxylic acid (COOH) group. The crystal structure is consolidated by C—H⋯O interactions. The H atoms of a methyl group of the caffeine molecule are disordered over two sets of sites of equal occupancy.